1991
DOI: 10.1104/pp.96.2.644
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum and Temperature Alteration of Cell Membrane Permeability of Quercus rubra

Abstract: This report extends research on Al-induced changes in membrane behavior of intact root cortex cells of Northern red oak (Quercus rubra). Membrane permeability was determined by the plasmometric method for individual intact cells at temperatures from 2 or 4 to 35°C. Al (0.37 millimolar) significantly increased membrane permeability to urea and monoethyl urea and decreased permeability to water. Al significantly altered the activation energy required to transport water (+32%), urea (+9%), and monoethyl urea (-7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…5). Although several reports have focused on the physical changes of artificial liposomes and PM (Deleers et al 1985;Suhayda and Haug 1986;Zhao et al 1987;Chen et al 1991), this is the first evidence suggesting the existence of an early strategy for A1 tolerance that is regulated by PM lipid. As the intact PM lipid bilayers differ in the com-position between inner and outer leaflet, the present permeability result can be accepted as the average characteristics of the reconstituted homogenous lipid bilayers of PM.…”
Section: Resultsmentioning
confidence: 75%
“…5). Although several reports have focused on the physical changes of artificial liposomes and PM (Deleers et al 1985;Suhayda and Haug 1986;Zhao et al 1987;Chen et al 1991), this is the first evidence suggesting the existence of an early strategy for A1 tolerance that is regulated by PM lipid. As the intact PM lipid bilayers differ in the com-position between inner and outer leaflet, the present permeability result can be accepted as the average characteristics of the reconstituted homogenous lipid bilayers of PM.…”
Section: Resultsmentioning
confidence: 75%
“…Interaction of Al with membrane components modifies the membrane structural properties such as fluidity and permeability (Khan et al 2009;Vierstra and Haug 1978;Wagatsuma et al 2005). In the root cortical cells of Northern red oak (Quercus rubra L.), it was found that Al decreased the membrane permeability to water (Chen et al 1991;Zhao et al 1987). Water absorption into the root cells is also controlled by the water potential gradient which acts as the driving force for water uptake and build-up of turgor which is a prerequisite for cell extension.…”
Section: Aluminium Toxicity and Root Water-relationsmentioning
confidence: 99%
“…Al is known to affect directly membrane structure and permeability (Vierstra and Haug, 1978;Haug, 1984;Zhao et al, 1987;Caldwell, 1989;Chen et al, 1991), and disruption of membrane transport processes can severely limit nutrient accumulation in the long term (Taylor, 1988a). However, for an observed response to A1 stress to be implicated in the inhibition of root growth, it must occur within the first few hours of exposure.…”
mentioning
confidence: 99%